2001
DOI: 10.1007/s00464-001-9017-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the surgeon's experience on the results oflaparoscopic hernia repair

Abstract: This study shows that postoperative complications, conversion rate, operating time, and recurrences are all substantially reduced as the surgeon's experience increases. Thus, once the learning curve is surpassed, TEP repair represents a good alternative to open techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 18 publications
3
45
0
5
Order By: Relevance
“…The mean operating time was 59 min in the first quartile of operations which gradually improved to 37 min in the fourth quartile. He also found Another study by Feliu-pala et al [15] showed that the mean operating time was >60 min for first 50 cases, but there was continuous decreasing trend as the level of experience increased (32 min for last 200 cases). Conversion to open or TAPP also decreased as the surgeons experience increased, being as high as 17 % for the first 100 cases and 2.2 % for the last 500 cases.…”
Section: Discussionmentioning
confidence: 81%
“…The mean operating time was 59 min in the first quartile of operations which gradually improved to 37 min in the fourth quartile. He also found Another study by Feliu-pala et al [15] showed that the mean operating time was >60 min for first 50 cases, but there was continuous decreasing trend as the level of experience increased (32 min for last 200 cases). Conversion to open or TAPP also decreased as the surgeons experience increased, being as high as 17 % for the first 100 cases and 2.2 % for the last 500 cases.…”
Section: Discussionmentioning
confidence: 81%
“…It is not clear whether laparoscopic surgery should be a superspecialty for a few surgeons or be performed by all general surgeons. Most surgeons with laparoscopic experience believed that the use of laparoscopic techniques should be generalized, although this issue continues to be controversial [2, 3, 4, 5, 6, 7, 8, 9]. Most of the surgeons who did not carry out advanced laparoscopic procedures pointed to the low number of patients in whom this would be performed, to resource or other local constraints as well as to the unwillingness to learn the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, advanced procedures were performed by only a few surgeons, despite the fact that most hospitals had adequate technical facilities and equipment, presumably due to the lack of evidence of their advantages over open surgery, coupled with the technical difficulty [5, 7, 9, 10]. Thus, the evidence base for advanced laparoscopic surgery needs to be expanded [4], and there should be better opportunities for training both for trainees and practicing specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51] The Cooperian philosophy is still timely and rather more true in the current laparoscopic era for safe and successful outcome as emphasized recently by Annibali et al and Bhatia, [52,53] and it demands crisp precise flawless anatomical knowledge, [16,26,53] long strenuous laparoscopic learning, [16,21] and significant laparoscopic experience of >30-80 cases, [27,[55][56][57][58][59] for the seamless surgery, and that it also poses new Section: Surgery dangers of modern technological approaches, warranting more anatomic research. [28,33] Anecdotal experiences published in the literature indicate that the fascial arrangements and relationships of structures near the deep inguinal ring are unfamiliar from the laparoscopic perspectives and are not generally known to most of the laparoscopic hernia surgeons.…”
Section: Discussionmentioning
confidence: 99%